Branch retinal artery occlusion post-penetrating globe injury with intraocular foreign body - Manish Nagpal (Indian Journal of Ophthalmology, 2018)
Intraocular foreign body (IOFB) in cases of penetrating eye injury accounts for an important indication of vitreoretinal intervention following ocular trauma. Vascular occlusion as a complication of IOFB is rare. Here we present a case of a 34-year-old male with post-traumatic cataract and an intraocular metallic foreign body (IOFB) lodged in the superficial layers of the retina inferotemporal to the disc, causing an inferotemporal branch retinal artery occlusion. The case was managed by lensectomy with pars plana vitrectomy and IOFB removal followed by a second procedure of secondary IOL implantation. Final best-corrected visual acuity improved to 6/24. This case highlights an unusual sequelae following penetrating ocular trauma.